PENGARUH INDPENDENSI DAN KOMPETENSI TERHADAP PENCEGAHAN FRAUD DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERATING - Munirah Rukayyah; Andi Wawo; Nur Rahma Sari (ISAFIR: Islamic Accounting and Finance Review, 2023)
The purpose of this study was to find out how independence and competence influence fraud prevention with emotional intelligence as a moderating variable at BPKP Representative for South Sulawesi Province. This study uses a quantitative method with a causality approach. This study uses subject data. The data source used is primary data. The data collection method was carried out using a questionnaire in the form of a written list of questions. The number of respondents used in this study were 37 people. Respondents in this study were auditors. The results of this study indicate that independence has a positive and significant effect on fraud prevention. Competence has a positive and significant effect on fraud prevention. Emotional intelligence does not moderate and weaken the effect of independence on fraud prevention. Emotional intelligence moderates the influence of competence on fraud prevention. Future research is expected to be able to develop this research by adding variables and expanding the object of research.